PROBLEMATIKA PEMANFAATAN BUKU PENDIDIKAN AGAMA ISLAM PADA SEKOLAH DASAR DI KABUPATEN MAMUJU: PROBLEMS IN THE USE OF ISLAMIC EDUCATION BOOKS IN ISLAMIC PRIMARY SCHOOL IN MAMUJU - Idham Idham (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
This study aims to know: 1) the conditions of primary schools in Mamuju regency, 2) the availability of Islamic Religious Education (PAI) books in primary schools, 3) the utilization mechanism of Islamic Religious Education textbooks in primary school, and the problems faced by educators and learners in utilizing PAI books in primary school. Using qualitative descriptive method, the study found that there is limited availability of PAI books in those schools; due to the fact that the curriculum 2013 has not implemented optimally. The acquisition of books evidently has been done through waiting for center to be distributed in schools. The limitation also hampered the use of PAI books either as required or recommended books. Although in some aspects, the schools independently acquire books to anticipate the fulfillment of teaching materials. Strengthening teachers capacity in terms of technical assistance has not been done evenly. This results in the lack of implementing knowledge for PAI primary school teachers in Mamuju. Keywords: Religious education book, Primary school, Educational policy, Mamuju Penelitian ini berangkat dari keinginan untuk mengetahui: 1) kondisi Sekolah Dasar di Kabupaten Mamuju, 2) ketersediaan buku Pendidikan Agama Islam di sekolah dasar, 3) mekanisme pemanfaatan buku- buku paket PAI di Sekolah Dasar serta problem yang dihadapi oleh pendidik dan peserta didik dalam memanfaatkan buku PAI di Sekolah Dasar. Melalui metode kualitatif deskriptif, penelitian ini menemukan keterbatasan ketersediaan buku PAI di sekolah sasaran, dikarenakan implementasi kurikulum 2013 yang masih belum maksimal yang ditandai dengan pengadaan buku yang masih â€œmenunggu distribusi dari pusatâ€ untuk disalurkan di sekolah. Keterbatasan itu pula yang menghambat pemanfaatan buku PAI, baik wajib maupun penunjang. Meski pada beberapa aspek, inisiatif pengadaan secara mandiri tetap dilakukan sebagai antisipasi pemenuhan bahan ajar. Penguatan kapasitas guru dalam hal bimbingan teknis juga masih belum dilakukan secara merata mengakibatkan keterbatasan pengetahuan implementatif dari mereka para guru-guru PAI Sekolah Dasar di Mamuju. Kata Kunci: Buku pendidikan agama, sekolah dasar, kebijakan pendidikan, Mamuju